The Role of Fluorine in F-La/TiO2 Photocatalysts on Photocatalytic Decomposition of Methanol-Water Solution - Edelmannova, Miroslava; Dubnová, Lada; Reli, Martin; Meinhardová, Vendula; Huo, Pengwei; Stangar, Urska Lavrencic; Čapek, Libor; Koci, Kamila (MDPI, 2019)
F-La/TiO2 photocatalysts were studied in photocatalytic decomposition water-methanol solution. The structural, textural, optical, and electronic properties of F-La/TiO2 photocatalysts were studied by combination of X-ray powder diffraction (XRD), nitrogen physisorption, Ultraviolet-visible diffuse reflectance spectroscopy (UV-Vis DRS), Electrochemical impedance spectroscopy (EIS), and X-ray fluorescence (XPS). The production of hydrogen in the presence of 2.8F-La/TiO2 was nearly up to 3 times higher than in the presence of pure TiO2. The photocatalytic performance of F-La/TiO2 increased with increasing photocurrent response and conductivity originating from the higher amount of fluorine presented in the lattice of TiO2.
Role fluoru v F-La/TiO2 fotokatalyzátorech na fotokatalytický rozklad vodného roztoku metanolu
Keywords: hydrogen production; fluorine; lanthanum; titanium dioxide; produkce vodíku; fluor; lanthan; TiO2